Realizing the Hayden-Preskill protocol with coupled Dicke models - Yanting Cheng; Chang Liu; Jinkang Guo; Yu Chen; Pengfei Zhang; Hui Zhai (Physical Review Research, 2020)
Hayden and Preskill proposed a thought experiment in which Bob can recover the information Alice throws into a black hole if he has a quantum computer entangled with the black hole, and for which Yoshida and Kitaev recently proposed a concrete decoding scheme. In the context of quantum many-body physics, the parallel question is that after a small system is thermalized with a large system, how can one decode the initial state information with the help of two entangled many-body systems? Here, we propose to realize this decoding protocol in a physical system of two Dicke models, with two cavity fields prepared in a thermofield double state. We show that the Yoshida-Kitaev protocol allows us to read out the initial spin information after it is scrambled into the cavity. We show that the readout efficiency reaches a maximum when the model parameters are tuned to the regime where the system is the most chaotic, characterized by the shortest scrambling time in the out-of-time-ordered correlation function. Our proposal opens up the possibility of discussing this profound thought experiment in a realistic setting.